Working and Learning in Times of Uncertainty: Challenges to Adult, Professional and Vocational Education (Research on the Education and Learning of Adults, 2015)
This book analyses the challenges of globalisation and uncertainty impacting on working and learning at individual, organisational and societal levels. Readership: Educational Researchers and their students